Answer: 484
===============================================
Work Shown:
First let's compute f(2). We replace every x with 2 and then use PEMDAS to simplify
f(x) = -x^4 + 5x - 4x^2
f(2) = -(2)^4 + 5(2) - 4(2)^2
f(2) = -16 + 5(2) - 4(4)
f(2) = -16 + 10 - 16
f(2) = -6 - 16
f(2) = -22
Then we square this result to find the value of
![[ f(2) ]^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/bdeo4edmf0fw9x2klohvhd5qxu6kzn6tll.png)
![f(2) = -22\\\\\left[ f(2) \right]^2 = [ -22 ]^2\\\\\left[ f(2) \right]^2 = 484](https://img.qammunity.org/2021/formulas/mathematics/high-school/zglmmsh6hx8pkvou95h7th5j7xf7j1bsyg.png)